2012
DOI: 10.7448/ias.15.3.17365
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequity in the lives of women involved in sex work in Kampala, Uganda

Abstract: BackgroundGender inequity is manifested in the social and economic burden women carry in relation to men. We investigate women's experiences of gender relations from childhood to adult life and how these may have led to and kept women in sex work.MethodsParticipants were drawn from an ongoing epidemiological cohort study of women working in high HIV/STI risk environments in Kampala. From over 1000 enrolled women, we selected 101 for a qualitative sub-study. This analysis focuses on 58 women who engaged in sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
68
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 37 publications
6
68
1
Order By: Relevance
“…Debriefs were conducted after each interview, which helped to inform the focus of subsequent interviews. This is a tried and tested approach and we have successfully conducted interviews without tape recorders with this population in our previous work (Mbonye, Nakamanya, Nalukenge, et al, 2013;Mbonye et al, 2012;Mbonye, Rutakumwa, Weiss, & Seeley, 2014). All personal identifiers were excluded from the detailed accounts.…”
Section: Methodsmentioning
confidence: 99%
“…Debriefs were conducted after each interview, which helped to inform the focus of subsequent interviews. This is a tried and tested approach and we have successfully conducted interviews without tape recorders with this population in our previous work (Mbonye, Nakamanya, Nalukenge, et al, 2013;Mbonye et al, 2012;Mbonye, Rutakumwa, Weiss, & Seeley, 2014). All personal identifiers were excluded from the detailed accounts.…”
Section: Methodsmentioning
confidence: 99%
“…Populations at risk include adolescents, sex workers and their clients, men who have sex with men, prisoners, truck drivers, fishing communities. Additionally, compared to men, women are at an increased risk of acquiring STI, a fact attributed to gender inequity and biological predisposition 11 . Despite efforts to control the spread of STIs, reports indicate an upward surge in the incidence of new cases 1 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Studies conducted in the different countries showed that the qualities of women's health were lower than that of men, and gender inequality (GI) and male dominant society are the main reasons. 9,10 Moreover, the UN has already declared the reduction of the GI as one of the developmental goals.…”
mentioning
confidence: 99%
“…Some studies reported that women being infected with HIV because of poverty and high risk affairs. 9,14 In addition, women living in developing countries have low knowledge of HIV morbidity, which is one of the factors of GI in these countries. 15 Whereas, WHO experts believe that evaluating the knowledge of HIV morbidity in communities can be helpful to reduce the number of people infected with HIV.…”
mentioning
confidence: 99%
See 1 more Smart Citation